Customer Perception and Satisfaction Towards Digital Banking Services: A Primary Survey of Nepalese Commercial Bank Users (Voice: A Biannual & Bilingual Journal, 2025)
Nepal has an extensive digitalization of banking services, which has transformed the customer banking experience, which has been particularly fast-tracked due to the COVID-19 pandemic. Nepalese commercial banks require a broad perception and satisfaction of customers to digital banking services so that they can enhance the quality of their services and competitive edge. It is on this basis that this study will explore customer perceptions and satisfaction levels towards digital banking services offered by commercial banks in Nepal and determine the major drivers that determine the level of adoption and satisfaction. It was done using a cross-sectional survey of 384 users of digital banking services of five major commercial banks in Nepal. The data was collected using the structured questionnaires using the convenience sampling method. Statistical tests included descriptive statistics, correlation analysis and Multivariate regression, and the SPSS version 26.0 was used. Findings showed that 78.4 per cent of the participants were generally satisfied with digital banking services. It was found that ease of use (b = 0.312, p < improving customer satisfaction), security features (b = 0.289, p < improving customer satisfaction), and reliability of the service (b = 0.267, p = 0.01) were predictors of customer satisfaction. However, issues related to the security of transactions (43.2%), as well as technical glitches (38.7%), proved to be the roadblocks. Even though the trend of digital banking is currently on the increase in Nepal, the banks need to resolve the security issues and improve the reliability of the system to increase customer satisfaction. The results of the study provide useful information to banking institutions and policy makers, thus helping the adoption of customer-oriented digital banking strategies.